Thallium Bromide Gamma-Ray Spectrometers and Pixel Arrays - Kim, Hadong; Ogorodnik, Yaroslav; Kargar, Alireza; Cirignano, Leonard; Thrall, Crystal Lynn; Koehler, William; O'Neal, Sean Patrick; He, Zhong; Swanberg, Erik; Payne, Stephen A.; Squillante, Michael R.; Shah, Kanai (Frontiers in Physics, 2020)
Thallium bromide (TlBr) is a compound semiconductor with a band gap of 2.68 eV making it ideal for room temperature radiation detection. The high atomic numbers, 81 and 35, and the high density of 7.56 g/cm3 give it excellent gamma-ray stopping power. TlBr is a cubic material that melts congruently at a relatively low temperature ( 480 C). These properties make it relatively easy to grow good quality crystals with high yield. As a result of improvements in the purification of TlBr mobility-lifetime product of electrons, µτe, is now on the order of 10-2 cm2/V, which is similar to that of CZT. High µτe enables the fabrication of thicker detectors with good charge collection and energy resolution. The properties of TlBr make it ideal for use in room temperature gamma radiation operation [Smith 2013]. Single carrier devices such as small pixel arrays [O'Neal 2018a] and Frisch collar devices [Hitomi, et al.2013] which were developed for CZT can also been applied to TlBr. For example, better than 1% FWHM at 662 keV has been obtained for single pixel events with small (e.g. 3 x 3 pixels, 1-mm pitch, 5-mm thick) arrays.